Heparin-mimetic sulfated peptides with modulated affinities for heparin-binding peptides and growth factors - Kim, Sung Hye (2007)
Heterogeneity in the composition and in the polydispersity of heparin has motivated the development of homogeneous heparin mimics, and peptides of appropriate sequence and chemical function have therefore recently emerged as potential replacements for heparin in selected applications. Here, we report the assessment of the binding affinities of multiple sulfated peptides (SPs) for a set of heparin-binding peptides (HBPs) and for vascular endothelial growth factor isoform 165 (VEGF165); these binding partners have application in the selective immobilization of proteins and in hydrogel formation through non-covalent interactions. Sulfated peptides were produced via solid-phase methods, and their affinity for the HBPs and VEGF165 was assessed via affinity liquid chromatography (ALC), surface plasmon resonance (SPR), and in selected cases, isothermal titration calorimetry (ITC). The shortest peptide, SP(a), showed the highest affinity binding of HBPs and VEGF165 in both ALC and SPR measurements, with slight exceptions. Of the investigated HBPs, a peptide based on the heparin-binding domain of human platelet factor 4 showed greatest binding affinities toward all of the SPs, consistent with its stronger binding to heparin. The affinity between SP(a) and PF4(ZIP) was indicated via SPR (K(D) = 5.27 μM) and confirmed via ITC (K(D) = 8.09 μM). The binding by SP(a) of both VEGF and HBPs suggests its use as a binding partner to multiple species, and the use of these interactions in assembly of materials. Given that the peptide sequences can be varied to control binding affinity and selectivity, opportunities are also suggested for the production of a wider array of matrices with selective binding and release properties useful for biomaterials applications.